Виявлення дронів за допомогою комп’ютерного зору як елемент захисту конфіденційної інформації - Шевченко, О. Т. (ХНУРЕ, 2024)
This paper addresses the crucial issue of confidential information security in the context of the rapidly evolving technological landscape, focusing on the challenges posed by the unauthorized use of unmanned aerial vehicles (UAVs), or drones. The increased accessibility and sophistication of drones have escalated the risks to privacy and security across various sectors, including military, commercial, state institutions, and private individuals. This situation underscores the urgency of developing reliable drone detection methods.
Keywords: виявлення дронів; захист конфіденційної інформації